Projetos pedagógicos de curso: o que eles dizem sobre a educação do campo na formação de professores de Matemática - Raminelli, Carlos Daniel (2024)
This research, with a qualitative approach, aims to carry out a survey and subsequent analysis of the Projects Pedagogical Projects of Courses at Federal Universities in the states of Rio Grande do Sul, Santa Catarina and Paraná that have a Mathematics Degree course in face-to-face modality, with the purpose of finding the reference for the Field Education modality. In addition to presenting, if any, Rural Education references, it also intends to discuss how these are found. To support the studies, some issues relating to Field Education and Rural Education are addressed, as well as Teacher Training and the impact of the curriculum on this training. The data collection and analysis methodology, the Pedagogical Course Projects, are also described. The evidence found is identified and occurs based on explicit mentions in the curriculum matrices. The final considerations present the discussion of the elements, making it possible to observe the presence of evidence, for the most part, in internship subjects and which discuss pedagogical practices, Field Education being a diverse aspect to be discussed, not as a priority and central theme within the educational debate.